Seismic soil structure interaction response of elastic and inelastic moment resisting framed structures on embedded rafts - Anand, Vishwajit; Kumar, S.R. Satish (Journal of Structural Engineering, 2024)
A structure subjected to operational dynamic loads or moderate levels of ground shaking is expected to remainelastic. However under severe earthquakes, which are not very frequent, the same structure is designed to exhibitinelastic behaviour and sustain some damage so as to achieve an economical design. This dual strategy of seismicdesign makes understanding of elastic as well as inelastic behaviour of structures important. The present study devisesan algorithm to assess effects of soil-structure interaction on elastic and inelastic seismic response of structures withkinematic hardening using the substructure approach. The critical step involved in this approach is the determinationof dynamic impedance functions. The dynamic impedance functions have been obtained from literature. Whereverrequired, plots in Gazetas (1991) have been digitized to obtain polynomial expressions. The dynamic analyses on SDOFidealizations of structures have been performed in MATLAB using Newmark γ-β method. Effects of few engineeringdesign parameters, which encompass material and geometrical properties of a soil-structure system, on the structuralresponse of SSI systems have also been explored. The present study is restricted to moment resisting framed reinforcedconcrete buildings founded on embedded raft foundations.